1994
DOI: 10.1007/bf00866346
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation in children with emphasis on young patients

Abstract: We report the results of 41 consecutive renal transplantations performed on 39 children (median age 2.7 years). Twenty-six recipients were less than 5 years old. Twenty-one recipients (13 under the age of 5 years) received cadaver (CAD) grafts. All grafts except 2 were from adult donors and were placed extraperitoneally. Patients were on triple immunosuppression (cyclosporine plus azathioprine plus methylprednisolone). Mean follow-up time was 2.3 years. No vascular and only one ureteral complication was seen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
5
15
0
Order By: Relevance
“…Patient survival in our center is comparable with others [6,8]. Laine et al [6] reported 100% patient survival at 3 years and Najarian et al [8] 97% at 1 and 3 years, and 95% at 5 years. However others have reported lessimpressive outcomes [7], particularly in infants [15].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Patient survival in our center is comparable with others [6,8]. Laine et al [6] reported 100% patient survival at 3 years and Najarian et al [8] 97% at 1 and 3 years, and 95% at 5 years. However others have reported lessimpressive outcomes [7], particularly in infants [15].…”
Section: Discussionsupporting
confidence: 88%
“…It is usually followed by an improvement in growth [10] and psychomotor development [11]. Patient survival in our center is comparable with others [6,8]. Laine et al [6] reported 100% patient survival at 3 years and Najarian et al [8] 97% at 1 and 3 years, and 95% at 5 years.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Increased incidence of graft loss due to vascular thrombosis in younger children has been reported [9]. However, in recent years excellent results of renal transplantation have been reported in children under 5 [12,13,16]. In a large series from Minnesota, Najarian and coworkers [15] reported a 5-year graft survival rate using LRD of 73% in 75 infants under 2 years of age.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the treatment of infants and young children remains controversial. Some authors reported excellent results with renal transplantation [12,16] whereas others discussed poor outcome after cadaveric donor (CAD) transplantation and increased incidence of graft vessel thrombosis [9].…”
Section: Introductionmentioning
confidence: 99%